PERAN PEMASARAN DIGITAL DALAM MENINGKATKAN PENDAPATAN USAHA AHA KEBAB DI KELURAHAN SIPOLU-POLU KECAMATAN PANYABUNGAN KABUPATEN MANDAILING NATAL - Darwin Nasution; Rizki Amalia (LPPM STAI Muhammadiyah Probolinggo, 2026)
Digital marketing is a form of marketing evolution that utilizes digital media as the primary channel for delivering product and service information to consumers. Through digital marketing, more effective two-way communication can be established between businesses and consumers, which has the potential to increase business revenue. This study aims to analyze the effect of digital marketing on revenue growth at AHA Kebab business located in Sipolu-polu Village, Panyabungan District, Mandailing Natal Regency. The research employed a quantitative method with the population consisting of all AHA Kebab consumers during the period of January to August 2025. The sample comprised 96 respondents selected using the accidental sampling technique. Data were collected through observation, documentation, and questionnaires. Data analysis was conducted using validity test, reliability test, normality test, heteroscedasticity test, simple linear regression analysis, partial test, and coefficient of determination with the assistance of SPSS version 21. The results indicate that digital marketing has a positive and significant effect on revenue growth with a significance value of 0.000 < 0.05. The coefficient of determination of 0.649 shows that 64.9% of revenue increase is influenced by digital marketing, while 35.1% is affected by other factors. Therefore, effective implementation of digital marketing can significantly improve business revenue.